Carbon leakage in a small open economy with capital mobility - Roberto Roson (Fondazione Eni Enrico Mattei (FEEM), 2001)
The carbon emissions abatement, undertaken by some countries, may induce other countries to increase their own emissions. This effect, known as "carbon leakage", may be due to rather different mechanisms. The simplest case is when outside countries do not change their environmental policies and world prices are fixed. Unilateral policies may then induce a substitution of domestic production, generating emissions, with imports.This paper analyses the carbon leakage generated under the "small open economy" assumption, illustrating some findings through a numerical, dynamic, general equilibrium model of the Italian economy. The analysis highlights two main points. First, in a general equilibrium setting, the carbon leakage depends on both the substitution and income effects. Income effects, in turn, crucially depend on how carbon tax revenues are recycled, or pollution rights rents are assigned. Different recycling schemes have rather different impacts on the national income and on the trade-induced leakage. Second, carbon leakage may be significantly affected by the degree of capital mobility in international markets, because capital services enter the balance of trade. Capital outflows amount to exports of capital services, possibly financing the import of carbon-intensive goods. This result suggests that, in a world of increasingly integrated financial markets, unilateral environmental policies are becoming less effective, because of the existence of policy spill-overs.
Keywords: D31; D58; D91; E62; Q28; 330; Carbon leakage; Computable General Equilibrium; carbon taxation; capital mobility; Klimaschutz; Ökosteuer; Treibhausgas-Emissionen; Kleine offene Volkswirtschaft; Kapitalmobilität; Dynamisches Gleichgewicht; Theorie; Italien